2018
DOI: 10.1007/s11540-018-9394-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Positive Selection on Incidence of Different Viruses During Multiple Generations of Potato Seed Tubers in Uganda

Abstract: Smallholder farmers in Uganda commonly use seed potato tubers from the informal sector, especially by seed recycling over several generations. Therefore, seed tubers are highly degenerated with viruses and other pathogens, resulting in poor yield and quality of the produce. Over one cycle of multiplication, degeneration management by positive seed selection was found to be efficient in reducing virus diseases compared with the farmers' method of selection. The objective of this study was to assess to what exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 15 publications
2
37
0
2
Order By: Relevance
“…Just like in this study, limited knowledge of plant viruses as opposed to other pathogens has been reported by other authors working on different crops elsewhere (Colvin et al 2012;Adam et al 2015 (Mendez-Lozano et al 2003). Knowledge of virus symptoms can help farmers know when their crop is infected so that they can take appropriate actions like negative selection, positive selection (Priegnitz et al 2019) or replace infected seed tubers with disease free certified seed tubers among other methods.…”
Section: Farmer's Knowledge Of Virus Symptoms and Vector Virus Transmmentioning
confidence: 74%
See 4 more Smart Citations
“…Just like in this study, limited knowledge of plant viruses as opposed to other pathogens has been reported by other authors working on different crops elsewhere (Colvin et al 2012;Adam et al 2015 (Mendez-Lozano et al 2003). Knowledge of virus symptoms can help farmers know when their crop is infected so that they can take appropriate actions like negative selection, positive selection (Priegnitz et al 2019) or replace infected seed tubers with disease free certified seed tubers among other methods.…”
Section: Farmer's Knowledge Of Virus Symptoms and Vector Virus Transmmentioning
confidence: 74%
“…All these previous surveys indicated that PVY is one of the most important viruses in Kenya due to the high prevalence reported over the past decades. Virus surveys in the neighboring countries like Tanzania (Chiunga 2013), Uganda (Gildemacher et al 2009;Priegnitz et al 2019) and Ethiopia (Gildemacher et al 2009) similarly report PVY as one of the major viruses in the potato production systems in these countries.…”
Section: Occurrence Of Potato Viruses In Kenyamentioning
confidence: 99%
See 3 more Smart Citations